A Case of Acute Life-Threatening Pulmonary Hemorrhage from Synthetic Cannabinoid Abuse. (20th May 2019) - Imtiaz, Muhammad; Saha, Biplab; Sana Ullah, Uzma; Saha, Aditi
Abstract : We report a case of alveolar hemorrhage secondary to inhalation of synthetic cannabinoid. The patient developed hemoptysis and respiratory failure 48 hours after the episode. Alveolar hemorrhage from synthetic cannabinoid use is a rare entity that has been reported only thrice previously. The unique feature of this case was that the initial urine and blood toxicology screens were negative for cannabinoids and the diagnosis was confirmed via detection of serum metabolites of a synthetic cannabinoid.